Types of Road Traffic Accidents and Emergency Medical Care - Basri Lenjani; Agron Dogjani; Luljeta Abdullahu; Arlind Zeqiri; Dardan Lenjani; Bujar Imeri (Albanian Journal of Trauma and Emergency Surgery)
Introduction: A traffic accident is when only material damage is caused to the vehicle and track environment, and there are no casualties. RTA represents a significant risk for morbidity and mortality in Kosovo, of which head injury and multiple-site injury increase injury severity.